PENGARUH LINGKUNGAN KERJA DAN STRES KERJA TERHADAP KINERJA KARYAWAN PD. DHARMA JAYA - Ariska Damayanti; Iwan Kurniawan Subagja (Jurnal Manajemen Bisnis Krisnadwipayana, 2023)
This study aims to determine and analyze 1) The effect of the work environment on employee performance, 2) The effect of work stress on employee performance, 3) The effect of work environment and work stress on employee performance. The research was conducted on PD. Dharma Jaya, with a research sample of respondents from employees PD. Dharma Jaya. The type of research used in this research is quantitative research with a descriptive approach using multiple linear regression analysis. The research results show that 1) the work environment has a significant and positive effect on the performance of employees in PD. Dharma Jaya, 2) work stress has a significant and negative effect on the performance of employees in PD. Dharma Jaya, 3) work environment and work stress have a significant and positive effect on the performance of employees in PD. Dharma Jaya.